Fractional resurfacing in the Asian patient: Current state of the art. Issue 1 (8th September 2016) - Wat, Heidi; Wu, Douglas C.; Chan, Henry Hin Lee
Abstract : Background and Objective: Fractionated photothermolysis (FP) has revolutionized modern laser technology. By creating selective columns of microthermal damage, fractionated devices allows for greater treatment depths to be achieved without the prolonged downtime and risk of complications seen in traditional fully ablative laser resurfacing. Fractional resurfacing is a proven method to treat a variety of cutaneous conditions. In the Caucasian patient, a wide range of devices and treatment settings can be utilized safely and effectively. However, ethnic skin requires special consideration due to its unique pigmentary characteristics and clinical presentations. In this review article, we detail the current indications and strategies to optimize results and mitigate complications when utilizing fractional resurfacing for the Asian patient. Methods: A review of the MEDLINE English literature was conducted on fractionated laser devices studied in the Asian population. Articles included describe non‐ablative devices including fractionated erbium glass, thulium fiber, diode, and radiofrequency devices; and ablative devices including fractionated carbon dioxide (CO2 ) laser, erbium yttrium aluminum garnet and yttrium scandium gallium garnet (YSGG) laser. These data were integrated with the expert opinion of the authors. Conclusion: Taking into account the unique characteristics and cosmetic concerns of the Asian population, fractional resurfacing can be considered a safe and effective option for the treatment of atrophic and hypertrophic scarring, and photorejuvenation in ethnic skin types. Select cases of melasma may be treated with fractionated non‐ablative devices, but utilized with caution. The predominant complication associated with fractional resurfacing for these conditions is post‐inflammatory hyperpigmentation (PIH) and rebound worsening of melasma. A greater number of treatments at lower density settings and wider treatment intervals typically produce the lowest risks of PIH without compromising treatment efficacy. Lasers Surg. Med. 49:45–59, 2017. © 2016 Wiley Periodicals, Inc.